DAMPAK COVID-19 TERHADAP PEREKONOMIAN INDONESIA - Zulkipli Zulkipli; Muharir Muharir (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2021)
Since the beginning of 2020, to be precise in March, Indonesia has been shocked by one of the phenomena, namely the Covid-19 pandemic. As of August 2020, the total cases in Indonesia were 165,887 with 7,169 deaths in 34 provinces. The spread and increase in the number of Covid-19 cases occurring at a very fast time will have an impact on the decline in the Indonesian economy. This study aims to look at policies undertaken by the government for current disasters and see the economic impact that has occurred in Indonesia. This research shows that the policies made by the government in handling Covid-19 can indirectly lead to a decline in economic growth in Indonesia. The impact on the economic sector due to the Covid-19 pandemic in Indonesia includes layoffs, the occurrence of PMI Manufacturing Indonesia, decreased imports, increased prices (inflation) as well as losses in the tourism sector which led to a decrease in occupancy. As a result of this, it is hoped that the Indonesian government will be more alert in reducing economic growth in Indonesia as a result of the Covid-19 pandemic.